Coagulation Dynamics in Factor V Deficiency: A Family Study, with a Note on the Occurrence of Thrombophlebitis, , - Miller, Sherwood P.; with the technical assistance of Joanna Siggerud and Tadeusz Stefanski, B. S. (Thrombosis and Haemostasis, 1965)
1. A family with congenital proaccelerin (factor V) deficiency is here reported. The mode of inheritance appears to be by means of an autosomal recessive gene. The homozygous propositus (proaccelerin less than 2% of normal) had a life-long, moderately severe, bleeding tendency. The heterozygotes (proaccelerin 45 to 66%) were clinically normal.2. Studies on the rate of consumption of coagulation factors during blood clotting revealed normal consumption of antihemophilic globulin (factor VIII), but defective consumption of prothrombin (II) in the propositus. This indicated the entry of proaccelerin into the clotting process between the stages at which antihemophilic globulin and prothrombin are involved. Five of the seven heterozygotes studied showed a similar pattern. These findings are consistent with current theories of the role of proaccelerin in the normal sequence of events in the coagulation scheme.3. The propositus had an episode of thrombosis of the deep saphenous vein which is apparently a unique occurence in the literature of proaccelerin deficiency.